Variations of Middle Turbinate in Chronic Rhinosinusitis - Dhungana, Anup; Mishra, Sumedh; Joshi, Rupesh Raj; Shrestha, Shivani; Poudel, Bishal (Nepal Medical College Journal, 2025)
Chronic rhinosinusitis (CRS) is a prevalent inflammatory condition of the nasal and paranasal sinuses lasting more than 12 weeks. Anatomical variations of the middle turbinate, particularly concha bullosa and paradoxical curvature, have been proposed as potential contributing factors to CRS by affecting sinus ventilation and mucociliary clearance. This study aims to evaluate the prevalence of middle turbinate variations in patients with CRS using computed tomography (CT) imaging. A cross-sectional observational hospital based descriptive study was conducted at Nepal Medical College Teaching Hospital from March to November 2024. A total of 84 adult patients diagnosed with CRS based on clinical and radiological criteria were included. Patients with prior nasal surgery, trauma, or other sinonasal pathologies were excluded. Detailed nasal examinations and coronal CT scans were performed to assess middle turbinate anatomy. Of the 84 patients, 47 (56.0%) were male and 37 (44.0%) female, with a mean age of 38.17 ± 14.26 years. Concha bullosa was observed in 27.0% of patients, paradoxical middle turbinate in 5.0%, while 68.0% showed no variations. Middle turbinate variations were more frequent in males than females; however, the difference was not statistically significant. Middle turbinate variations, particularly concha bullosa, are relatively common in patients with CRS but do not show a statistically significant association with disease occurrence. Although these anatomical features may not independently cause CRS, their identification remains important for accurate diagnosis and surgical planning.